Surface Properties of Powder Injection Moulded Parts Related to Processing Conditions - Hausnerova, Berenika; Sanetrnik, Daniel; Pata, Vladimir (Manufacturing Technology Journal, 2018)
The surface quality of ceramic items produced via powder injection moulding (PIM) at processing conditions varying in injection moulding temperature and debinding route is investigated. The analysis is performed on aluminium oxide part design containing complicated rotational areas, where a smooth surface of an internal spiral is a critical quality factor. Surface properties of the final sintered parts are examined with the help of a contactless scanner. Then, the obtained surface roughness data are treated with suitable statistical analytical tools in order to reveal the effect of the processing conditions during the PIM process on the final parts. Relating surface properties of final sintered parts to processing parameters might provide a powerful tool to control particular steps of PIM process.
Keywords: Quality; Powder injection moulding; Contactless scanning; Roughness evaluation